Graphene dispersions in alkanes: toward fast drying conducting inks. Issue 28 (5th July 2017) - Al Shboul, A.; Trudeau, C.; Cloutier, S.; Siaj, M.; Claverie, J. P.
Abstract : A highly conducting graphene ink that dries immediately. Abstract : Graphene inks are becoming widely popular. However the vast majority of these inks are formulated in polar solvents with high-boiling points. Their slow evaporation is a bottleneck factor in roll-to-roll printing processes. Here, we developed a highly-conductive fast-drying graphene ink in isooctane, a non-polar and low-boiling solvent. For this purpose, a diblock copolymer containing pendant cholesterol groups was used during the exfoliation of natural graphite in isooctane. The polymer develops non-covalent supramolecular interactions with the graphene conjugated system, resulting in the formation of stable graphene dispersions (up to c = 4 mg mL −1 ). These dispersions were used for direct writing on a variety of substrates, and were shown to dry instantly after application. The influence of polymer concentration on graphene characteristics, on colloidal stability and on electrochemical characteristics has been studied. The lowest sheet resistance (80 Ω □ −1 ) was obtained when 23% of the graphene surface was covered by the polymer. In this case, the flakes were constituted of 2–5 graphene layers. More extensive exfoliation, down to single-layer graphene, was achieved at greater surface coverage, but led to inks with higher sheet resistance. Thus, by combining a tailored polymeric dispersant, a smooth exfoliation process and a low-boiling non-polar ink solvent, we were able to prepare highly-conductive fast-drying graphene inks which should have a high potentital for the development of roll-to-roll printed electronics.